Effects of passive smoking on the health of children and adolescents: a systematic review (Research, Society and Development, 2021)
Despite growing global efforts to control tobacco use, it remains a common addiction. Passive smoking is the inhalation of smoke from tobacco derivatives by non-smokers, breathing in the same toxic substances that the smoker inhales. The objective of this systematic review was to identify the possible effects of passive smoking on the health of children and adolescents. The PICO tool was used to prepare the research question. The protocol of this study was submitted to PROSPERO and the PRISMA guidelines were followed. The following databases were used: LILACS, MEDLINE and EMBASE. As a result, 493 articles were identified from the last 5 years, 8 articles were removed for being duplicates, 439 articles were excluded for not meeting the inclusion criteria, 8 articles were excluded for poor methodological quality and 38 were included in the study.  It was concluded, as evidence, that passive smoking has negative effects on the health of children and adolescents and was associated with respiratory, infectious, psychoneurocognitive, metabolic, cardiovascular, otorhinolaryngological, allergic disorders and increased mortality.